2017
DOI: 10.4085/1062-6050-52.6.01
|View full text |Cite
|
Sign up to set email alerts
|

The Ability of an Aftermarket Helmet Add-On Device to Reduce Impact-Force Accelerations During Drop Tests

Abstract: Context:  The Guardian Cap provides a soft covering intended to mitigate energy transfer to the head during football contact. Yet how well it attenuates impacts remains unknown. Objective:  To evaluate the changes in the Gadd Severity Index (GSI) and linear acceleration during drop tests on helmeted headforms with or without Guardian Caps. Design:  Crossover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Although several companies market helmets that claim to protect against concussion, a lack of published scientific literature exists, due in part to the proprietary nature of the products of helmet companies. Studies have been published that evaluate several innovations, such as tethering a helmet to shoulder pads [109] or introducing an additional layer on top of a helmet, but show limited scientific evidence supporting the clinical benefit of implementing these new designs. Specifically, Breedlove and colleagues evaluated the Guardian Cap and demonstrated that the device reduced force at velocities high enough to cause skull fracture, but failed to mitigate impact forces at the low and medium velocities typically involved in concussion [110].…”
Section: Future Directionsmentioning
confidence: 99%
“…Although several companies market helmets that claim to protect against concussion, a lack of published scientific literature exists, due in part to the proprietary nature of the products of helmet companies. Studies have been published that evaluate several innovations, such as tethering a helmet to shoulder pads [109] or introducing an additional layer on top of a helmet, but show limited scientific evidence supporting the clinical benefit of implementing these new designs. Specifically, Breedlove and colleagues evaluated the Guardian Cap and demonstrated that the device reduced force at velocities high enough to cause skull fracture, but failed to mitigate impact forces at the low and medium velocities typically involved in concussion [110].…”
Section: Future Directionsmentioning
confidence: 99%
“…The study of laboratory-based design of novel helmets for football has been sparse. 2,25 Nakatsuka and Yamamoto 25 added a soft cushion layer to the helmet exterior in an attempt to reduce the magnitude of head impacts. One helmet had a foam pad fixed to the crown and struck a second helmet with a foam pad fixed to the side, and after 90 total impacts, the foam layer of both helmets significantly reduced head impact–severity measures.…”
Section: Discussionmentioning
confidence: 99%
“…25 However, the study was limited by the low forces (30 g ) used, lack of rotational acceleration testing, and absence of a statistical analysis. Most recently, Breedlove et al 2 found that the addition of an outer cap to a commonly used football helmet did not reduce rates of linear acceleration significantly after subjecting it to 18 total tests on 6 locations at 3 different velocities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations